Factor Related to Women's Delay in Undergoing Breast Cancer Examination at Dr. H. Andi Abdurrahman Noor Tanah Bumbu Regional Hospital - eva mismaya wahyu ariyanti; Rusmilawaty Rusmilawaty; Rubiati Hipni; Erni Yuliastuti (JURNAL KEBIDANAN BESTARI, 2025)
Introduction: Delayed examination is the subject's delay in checking themselves to a health facility or medical professional, after realizing the signs and symptoms of breast cancer. From several studies that concluded that the delay in examination ≥3 months, based on the register data, monthly reports and medical records of RSUD dr. H. Andi Abdurrahman Noor Tanah Bumbu, most of the research subjects experienced late examination. The aim of this study is to Analyzing Factors Associated with Women's Delay in Undergoing Breast Cancer Screening. Methods: This research uses an analytical survey, with a cross-sectional approach. The population in this study was all 149 women who had breast cancer who underwent examination, taken using the Total Sampling Technique. Education, Pain/Pain Complaints, Health Insurance, and Affordability of Health Facilities. The dependent variable is the delay in women undergoing breast cancer examination. Collection and use of Secondary Data. Data were analyzed using the chi square test with significance α=0.05. Results: The majority of study subjects experienced a delay in breast cancer examination ≥3 months (52.3%), were highly educated (45%), experienced pain complaints (53%), had health insurance (54.4%), and the accessibility of health facilities was very far (82.6%). There was a significant relationship between delay and education (p-value = 0.004), delay with complaints of pain (p-value = 0.010; OR = 0.39), delay with health insurance (p-value = 0.008; OR = 2.58), delay with accessibility of health facilities (p-value = 0.001). Conclusion: There is a relationship between delays in breast cancer screening and education, complaints of pain, health insurance, and affordability of health facilities. Keyword: Factors, Delayed Examination, Breast Cancer.